2016
DOI: 10.1016/j.ebiom.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Offers Stronger Protection Than Sickle Cell Trait Against the Erythrocytic Stage of Falciparum Malaria and This Protection Is Reversed by Iron Supplementation

Abstract: BackgroundIron deficiency causes long-term adverse consequences for children and is the most common nutritional deficiency worldwide. Observational studies suggest that iron deficiency anemia protects against Plasmodium falciparum malaria and several intervention trials have indicated that iron supplementation increases malaria risk through unknown mechanism(s). This poses a major challenge for health policy. We investigated how anemia inhibits blood stage malaria infection and how iron supplementation abrogat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 27 publications
(39 reference statements)
7
57
0
Order By: Relevance
“…The same group has recently shown this to be true in Gambian children and that it applies both to laboratory and local clinical strains of P. falciparum (Goheen et al , 2016). They have further shown that young erythrocytes are more susceptible to invasion and propagation by P. falciparum merozoites than mature erythrocytes (Clark et al , 2014a,b; Goheen et al , 2016).…”
Section: Safety Of Antenatal Iron Interventions In Malaria‐endemic Sementioning
confidence: 88%
See 2 more Smart Citations
“…The same group has recently shown this to be true in Gambian children and that it applies both to laboratory and local clinical strains of P. falciparum (Goheen et al , 2016). They have further shown that young erythrocytes are more susceptible to invasion and propagation by P. falciparum merozoites than mature erythrocytes (Clark et al , 2014a,b; Goheen et al , 2016).…”
Section: Safety Of Antenatal Iron Interventions In Malaria‐endemic Sementioning
confidence: 88%
“…The same group has recently shown this to be true in Gambian children and that it applies both to laboratory and local clinical strains of P. falciparum (Goheen et al , 2016). They have further shown that young erythrocytes are more susceptible to invasion and propagation by P. falciparum merozoites than mature erythrocytes (Clark et al , 2014a,b; Goheen et al , 2016). Seven weeks of iron supplementation completely abrogated the protection offered by iron deficiency anaemia in both Gambian children (Goheen et al , 2016) and pregnant Gambian women (Drs Goheen, Bah & Cerami, MRC Unit The Gambia, Banjul, The Gambia, personal communication).…”
Section: Safety Of Antenatal Iron Interventions In Malaria‐endemic Sementioning
confidence: 88%
See 1 more Smart Citation
“…This has been driven by the hazardous nature of iron; both in causing oxidative damage and in promoting the growth of microorganisms. There is clear evidence that a moderate degree of iron deficiency anemia is highly protective against malaria [28] and likely protective against a range of bacterial and fungal pathogens [23] and possibly viruses [41] . This has resulted in the evolution of exquisite systems for chaperoning iron and regulating its intake and organ distribution.…”
Section: Conclusion: Implications Of the New Molecular Insightsmentioning
confidence: 99%
“…Hepcidin-induced hypoferremia in circulating plasma protects against the acute threat of bacterial and yeast sepsis. Prolonged upregulation of hepcidin leads to the anemia of inflammation or of chronic infection [27] , which in turn protects against the blood stage of malarial infection [28] . Similarly, hypoferremia in hepatocytes protects against the hepatic stages of malaria infection [29] .…”
Section: Competing Control Of Iron By Iron Needs and Infection/inflammentioning
confidence: 99%